The Tumor Immune Microenvironment plays a Key Role in Driving the Progression of Cholangiocarcinoma - Zhang, Ye; Yan, Hai-jiao; Wu, Jun (Current Cancer Drug Targets, 2024)
Cholangiocarcinoma (CCA) is an epithelial cancer distinguished by bile duct cell differentiation and is also a fibroproliferative tumor. It is characterized by a dense mesenchyme and a complex tumor immune microenvironment (TME). The TME comprises both cellular and non-cellular components. The celluar component includes CCA cells, immune cells and mesenchymal cells represented by the cancer-associated fibroblasts (CAFs), while the non-cellular component is represented by mesenchymal elements such as the extracellular matrix (ECM). Recent studies have demonstrated the important role of the TME in the development, progression, and treatment resistance of CCA. These cell-associated prognostic markers as well as intercellular connections, may serve as potential therapeutic targets and could inspire new treatment approaches for CCA in the future. This paper aims to summarize the current understanding of CCA's immune microenvironment, focusing on immune cells, mesenchymal cells, ECM, intercellular interactions, and metabolism within the microenvironment.
Keywords: tumor immune microenvironment